A comprehensive analysis of the defense responses of Odontotermes formosanus (Shiraki) provides insights into the changes during Serratia marcescens infection - Zhiqiang Wang; Mingyu Wang; Yujingyun Zhou; Kai Feng; Fang Tang (BMC Genomics)
Abstract Background Odontotermes formosanus (Shiraki) is a highly damaging agroforestry pest. Serratia marcescens is a broad-spectrum insecticidal pathogen and is highly lethal to O. formosanus. However, little is known about the mechanism between them. To improve the biological control of pests, a more in-depth analysis of the interactions between the pests and the pathogens is essential. Results We used RNA-seq, enzyme activity assays and real-time fluorescent quantitative PCR (qPCR) to explore the defense responses of O. formosanus against SM1. RNA-seq results showed that 1,160, 2,531 and 4,536 genes were differentially expressed at 3, 6 and 12 h after SM1 infection, and Kyoto Encyclopedia of Genes and Genomes (KEGG) results indicated that immune response and energy metabolism were involved in the defense of O. formosanus against SM1. Reactive oxygen species (ROS) levels and ROS synthesis genes were significantly elevated, and the antioxidant system were induced in O. formosanus after SM1 infection. In addition, the cellular immune genes were affected, and the Toll, immune deficiency (Imd), Janus kinase/signal transducer and activator of transcription (JAK/STAT), c-Jun N-terminal Kinase (JNK) and melanization pathways were activated. In vitro, Oftermicin, an antimicrobial peptide, had a significantly inhibitory effect on SM1. Furthermore, the expression levels and enzyme activities of phosphofructokinase (PFK), lactate dehydrogenase (LDH), succinate dehydrogenase (SDH) and isocitrate dehydrogenase (IDH) in glycolysis and tricarboxylic acid (TCA) cycles were increased. Conclusions Our results clearly demonstrated that O. formosanus defended against SM1 by activating the antioxidant system, innate immunity and energy metabolism. This study would provide useful information for the development of biological controls of O. formosanus.